Extended salvage surgery after high-dose chemoradiation therapy for tumors in the cervico-thoracic junction with invasion of the chest wall and the spine: a case series - Wiendieck, Kurt; Dörfler, Arnd; Sommer, Bjoern (Journal of Surgical Case Reports, 2022)
The treatment of malignant tumors localized in the upper thoracic cavity and involving the spine at the cervico-thoracic junction (CTJ) is challenging. We report on three patients with malignant tumors invading the thoracic inlet and the spine at the CTJ. All three patients underwent radical tumor resection and 360 degrees spine fusion following the posterior pedicle screw instrumentation and anterior vertebrectomy combined with implantation of an expandable titanium cage. Postoperatively, a mild paresis with hypesthesia of the ipsilateral arm occurred in one patient because of brachial plexus involvement. Two patients were still alive at last follow-up after 83 and 143 months, the third patient succumbed to tumor progression 13 months after extended salvage surgery. We display the possibilities of extended 'salvage' therapy in well-selected patients that were deemed hopeless regarding neurological function, biomechanical stability and tumor control after multiple courses of combined radio-chemotherapy.
CRIS-Team WoS Importer:2023-01-27